2000
DOI: 10.1002/pen.11339
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic apparent interpenetrating polymer networks of polyurethane and styrene/acrylic acid copolymer obtained by melt mixing. Structure‐property relationships

Abstract: Thermoplastic apparent interpenetrating polymer networks (thermoplastic‐AIPNs) were prepared at several compositions by melting and pressing of crystallizable polyurethane (CPU), based on butylene adipate glycol (BAG), and styrene/acrylic acid random copolymer (S/AA). Structure‐property relationships in the thermoplastic‐AIPNs were investigated by means of wide‐angle and small‐angle X‐ray scattering (WAXS, SAXS), differential scanning calorimetry (DSC), dynamic mechanical thermal analysis (DMTA), thermally sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
4
12
0
1
Order By: Relevance
“…In previous work, we investigated the structure–property relationships in t‐IPNs prepared from a crystallizable polyurethane (CPU) and a random copolymer of styrene/acrylic acid (S/AA) 10–14. These mixtures were called thermoplastic apparent IPNs, t‐AIPNs, because S/AA was used in the acid form and not in the salt form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, we investigated the structure–property relationships in t‐IPNs prepared from a crystallizable polyurethane (CPU) and a random copolymer of styrene/acrylic acid (S/AA) 10–14. These mixtures were called thermoplastic apparent IPNs, t‐AIPNs, because S/AA was used in the acid form and not in the salt form.…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of these relationships is essential for optimizing composition and processing of materials to meet specific end‐use requirements. Both t‐AIPNs prepared by melt mixing of the components13, 14 and by casting from a common solvent10, 12 were investigated. The results by a variety of experimental techniques showed that the t‐AIPNs were microheterogeneous systems with contributions to microheterogeneity from both the heterogeneity of the individual polymers and the thermodynamic incompatibility of the components.…”
Section: Introductionmentioning
confidence: 99%
“…Some interactions between the components and their effect on the microphase structure of each other in thermoplastic AIPNs are realized, and wide-angle X-ray scattering (WAXS) and SAXS have been reported [212]. The mechanical properties of the thermoplastic AIPNs, density ρ, flow limit σ f , elasticity modulus E, and tensile strength σ , change nonadditively with composition, with extreme values at small contents (until 5-10%) of CPU or S-co-AA in compositions.…”
Section: Properties Of Thermoplastic Apparent Ipnsmentioning
confidence: 99%
“…Thermoplastic AIPNs of several compositions prepared by mechanical blending in a roll mill of crystallizable polyurethane (CPU) and styreneacrylic acid random copolymer (S-co-AA) have been investigated using different techniques by Vatalis et al [212,213]. The CPU was based on TDI (mixture of 2,4-and 2,6-isomers, molar ratio 65 : 35) and oligomeric buty-lene adipate glycol (BAG, MM 2000); the molar proportion of reagents was 1.01 : 1.00.…”
Section: Properties Of Thermoplastic Apparent Ipnsmentioning
confidence: 99%
See 1 more Smart Citation